THE SINGAPORE CONVENTION ON MEDIATED SETTLEMENT AGREEMENTS: A NEW STRING TO THE BOW OF INTERNATIONAL MEDIATION? - Silvestri, Elisabetta (Revista Eletrônica de Direito Processual, 2019)
The purpose of this essay is to present an overview of the major contents of the Singapore Convention, a treaty aimed at providing uniform enforcement mechanisms for the mediated settlement agreements by which international commercial disputes are resolved. O presente artigo tem o propósito de apresentar uma visão geral sobre os principais pontos da Convenção de Singapura, um tratato voltado a fornecer mecanismos uniformes de cumprimento de acordos decorrentes de mediação, através dos quais os litígios comerciais internacionais são solucionados.